Information Externalities in Bank Based Financing for Private Innovation - Can Specialization Overcome Asymmetries? - Daniel Höwer; Wolfgang Sofka (Verein für Socialpolitik, 2010)
Investments in R&D have been identified as a cornerstone for growth and competitive advantages of firms and whole economies. We investigate the role that a firm's main bank plays for its investment in R&D. Existing literature suggests that the inherent information asymmetries of R&D projects make them hardly applicable for bank lending. We challenge this assumption by arguing that banks are heterogeneous with regard to their information processing capabilities. They can benefit from information externalities arising from industry and geographical specialization in their overall loan portfolio. We combine finance as well as innovation management and economics literature to develop this argument. We test our theoretical framework for more than 7,500 firm observations in Germany and their R&D expenditures over a five year time period. A unique database allows us to construct the overall corporate client portfolio of the main bank for each of these firms. Our results show trade-offs in the degree and nature of bank specialization. Industry specialization of a firm's main bank has a u-shaped effect on its R&D investment. Regional specialization, though, has an inverse u-shaped effect. Recommendations on optimal firm-bank combinations for fostering R&D investment can be developed based on these results.
Keywords: O32; D21; D82; 330; Innovation; Banking; information asymmetries; micro-data